Workplace Challenges and their Impact on Quality of Life Among Women in Midlife and Beyond - Tariq, Nabia; Shahid, Anum; Malik, Asmara Ahmed; Khan, Najm us Saqib (Pakistan Armed Forces medical journal, 2025)
Objective: To identify workplace challenges experienced by women in midlife and beyond and determine the impact of these challenges on their Quality of Life. Study Design: Analytical cross-sectional study. Place and Duration of Study: Islamabad, Pakistan, from March to December 2023. Methodology: This study included working women between the ages of 45 to 65 years, who were invited to participate in an online survey hosted on Google Forms. The survey was a structed and validated questionnaire, comprising demographic details and questions related to time utilization, job satisfaction and facing workplace challenges. Results: The researchers enrolled 282 female participants from Islamabad, Pakistan, majority (160, 56.7%) of whom were between the ages of 45-50 years and reported having full-time employment (162, 57.4%). While most participants felt that they did not face organizational discrimination in their workplace (192, 68.1%), a lot of participants also responded that they had faced employment rejection due to being in midlife (176, 62.4%) and had taken extra efforts to maintain their appearance (149, 52.8%). Statistical tests were applied where p-value ≤0.05 was considered significant. Conclusion: Majority women reported no organizational discrimination at work, experienced no economic challenges and feared no age-related job threats. Participants who reported occasionally taking time off work for themselves and spent time frequently with family and friends felt no need to take early retirement indicating high job satisfaction.